FUNCTIONS OF EPITHET IN LITERATURE - Farmanov Gayrat (PEDAGOGS, 2024)
Abstract; Epithets are often used by writers to develop characters, as epithets can be used as a nickname or a title. There are endless ways that epithets can be used.